The hygienic hypothesis and transformations in etiological knowledge: from causal ontology to ontogenesis of the body - Dina Czeresnia
The objective of this article is to systematize the principal recent research results pertaining to the so-called hygienic hypothesis, which establishes an etiological link between the increasing incidence of allergic diseases and the decreasing incidence of infectious diseases in the industrialized countries of the Western world. The author contends that the current debate on the hygienic hypothesis indicates significant transformations in the understanding of disease etiology, perhaps even as important as the transformations in the 19th century during the process leading to the constitution of modern medicine and the identification of infectious disease causal agents.